The potential links between human gut microbiota and cardiovascular health and disease - is there a gut-cardiovascular axis? - Almeida, Cátia (2023)
Publisher Copyright: Copyright © 2023 Almeida, Gonçalves-Nobre, Alpuim Costa and Barata.